1994
DOI: 10.1021/la00017a028
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Aryl and Alkyl Isocyanides on Powdered Gold

Abstract: Diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) is used to examine the adsorption of phenyl isocyanide (PhNC), tert-butyl isocyanide (Bu*NC), and 1,4-phenylene diisocyanide (1,4-DINC) from methanol solution on gold powder. These studies indicate that the isocyanides bond end-on to a single gold atom through the terminal carbon atom of the isocyanide group. This structural assignment is based on a comparison of the v(NC) values of the isocyanides adsorbed on gold with those in (PhNC)-AuCl, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
109
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(126 citation statements)
references
References 0 publications
15
109
2
Order By: Relevance
“…This is particularly because 1,4-PDI, for instance, is known to adsorb on Au via only one of its two isocyanide groups. 41 The other isocyanide group is pendent with respect to the Au substrate, so that new Au or Ag nanoparticles can further bind onto it, forming a sandwich-type molecular nanostructure. As before, no Raman signal was observed when 1,4-PDI was self-assembled onto a flame-annealed Au wire, since it is SERS inactive.…”
Section: ·3 Surface Potential Of Metal Nanoparticlesmentioning
confidence: 99%
“…This is particularly because 1,4-PDI, for instance, is known to adsorb on Au via only one of its two isocyanide groups. 41 The other isocyanide group is pendent with respect to the Au substrate, so that new Au or Ag nanoparticles can further bind onto it, forming a sandwich-type molecular nanostructure. As before, no Raman signal was observed when 1,4-PDI was self-assembled onto a flame-annealed Au wire, since it is SERS inactive.…”
Section: ·3 Surface Potential Of Metal Nanoparticlesmentioning
confidence: 99%
“…Research was also conducted on the characteristics of the adsorption and self-assembled monolayers (SAM) of the alkyl and phenyl isocyanide by Raman and IR spectroscopy techniques. [12][13][14][15][16][17][18][19][20][21] It was found experimentally that the SAM of the isocyanide was located at the top site of the gold surface and bound in the terminal geometry on the gold, but the binding and the characteristics of the SAM were not understood well. Recently a few theoretical researches were conducted on the adsorption of isocyanide on gold.…”
Section: Introductionmentioning
confidence: 99%
“…[10] In a separate surfaceenhanced infrared absorption spectroscopy study, two peaks associated with the NC stretching vibration were identified at 2122 and 2169 cm À1 , indicating that the two isocyanide groups of 1,4-PDI are no longer equivalent in the adsorbed state. [11] For neat 1,4-PDI, the NC stretching band is observed at 2127 cm À1 in the normal Raman (NR) spectrum.…”
mentioning
confidence: 96%